World Agricultural Forum 2017 - Future of agriculture and implications for ASEAN - Ong, Keng Yong (2017)
Agriculture and food production seem to be under constant threat from climate change, policy failure and new diseases in meeting the demand of an ever increasing world population. Yet, innovative endeavours and technological advancements have given hope that adaptation, invention and international cooperation can overcome the looming challenges, with positive implications for ASEAN’s approach to food security.